Internet-Delivered Acceptance-Based Cognitive-Behavioral Intervention for Social Anxiety Disorder With and Without Therapist Support: A Randomized Trial. (September 2017) - Gershkovich, Marina; Herbert, James D.; Forman, Evan M.; Schumacher, Leah M.; Fischer, Laura E.
Social anxiety disorder (SAD) is one of the most prevalent psychiatric disorders in the United States. Although evidenced-based behavioral treatments are available, less than 20% of those with SAD receive treatment. Internet-based interventions can address barriers to treatment access, and guided Internet-based treatments have been demonstrated to be effective for SAD. However, the optimal role (if any) of the therapist in such programs remains unclear. We examined the acceptability and efficacy of a novel Internet-based cognitive-behavior therapy for SAD that utilizes traditional behavioral interventions (e.g., exposure) within the context of a model emphasizing mindfulness and psychological acceptance. Forty-two participants were randomized to an eight-module self-help intervention with ( n = 20) or without ( n = 22) adjunctive therapist support; the therapist support was delivered through 10 to 15 min of weekly videoconferencing and daily text messages. Both groups experienced a significant reduction in SAD symptoms and improvements in functioning and quality of life, with no significant differences between groups in both completer-only and intent-to-treat analyses. However, the therapist support group evidenced lower attrition than the minimal support group (20% vs. 50%). Implications for dissemination and future directions are discussed.